LIFESTYLE AND SELF-ESTEEM OF GENERATION Z IN GADGET PURCHASING DECISION - Eddy Madiono Sutanto; Stela Aubelia (Faculty of Economics and Business, University of Pasundan, 2022)
The consumer purchasing decision is one of the essential aspects for companies to assess the success of their products. Lifestyle and self-esteem can cause consumer purchasing decisions. This study aimed to find the dependencies between lifestyle and self-esteem with the decision to purchase gadgets by Generation Z. The type of research was quantitative research with a judgmental sampling technique. The samples were 100 respondents who had purchased a gadget at least once. This study used questionnaires to collect data and processed the chi-square test by SPSS 2.5. The results showed that lifestyle and self-esteem had a positive dependency relationship on consumer purchasing decisions.